A comparative analysis of protein virulence factors released via extracellular vesicles in two Candida albicans strains cultivated in a nutrient-limited medium. (November 2019) - Konečná, Klára; Klimentová, Jana; Benada, Oldřich; Němečková, Ivana; Janďourek, Ondřej; Jílek, Petr; Vejsová, Marcela
Abstract: One of the pathways for the delivery of virulence effector molecules into the extracellular environment of Candida albicans relies on the release of membrane-bound carriers which are called extracellular vesicles (EVs). Only a few studies aimed at investigating Candida albicans extracellular vesicles protein cargo and its potential contribution to the pathogenesis of C. albicans infections have been conducted to date. In this study, we mainly focused on a search for proteins with a demonstrated linkage to pathogenesis in EVs isolated from two C. albicans strains, the model strain ATCC 90028 and the clinical isolate from a woman suffering from vulvovaginal candidiasis. For the purpose of mimicking one of many hostile conditions during a host-pathogen interaction, C. albicans strains in a nutrient-limited medium were cultivated. We have hypothesized that this unfavourable, stressful condition could contribute to the induction of virulence effector molecules being released at a more extensive rate. In conclusion, 34 proteins with an undisputed linkage to C. albicans pathogenesis were detected in the extracellular vesicle cargoes of both strains. In case of the clinical isolate strain, no unique virulence-associated proteins were detected. In the C. albicans ATCC 90028 model strain, three unique proteins were detected, namely: agglutinin-like protein 3 (Als3), secreted aspartic protease 8 (Sap8) and cell surface superoxide dismutase [Cu–Zn] 6 (Sod6). Graphical abstract: Image 1 Highlights: Stress response was induced in two C. albicans strains in nutrient-limited medium. 34 proteins with a linkage to C. albicans pathogenesis were detected in the EVs. Sap7 was successfully identified only in EVs cargo of the clinical isolate strain. In C. albicans ATCC 90028, 3 unique proteins were detected: Als3, Sap8 and Sod6.